2017
DOI: 10.15766/mep_2374-8265.10613
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Care: Improving the Quality of Discharge Summaries Completed By Internal Medicine Residents

Abstract: Introduction: Discharge summaries are now the accepted means of communication in transition from inpatient to ambulatory care. However, there is often no formal residency education on this critical document, leading to discordance in discharge summaries written by internal medicine residents. There is little in the literature focusing on teaching how to effectively create a discharge summary using an electronic health record (EHR). Methods: A 1-hour workshop was designed to teach components of the discharge su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Prior studies were limited by their use of resident educational curricula to improve discharge summaries; however, the EHR template described here uses repeated, system-level reinforcement embedded into the workflow to train residents on care transition priorities. [27][28][29] The 8-item template (Figure 2) addresses common discharge summary deficiencies reported in previous studies and confirmed in our focus groups. 6,15 Each item was created in response to PCP feedback: some items steer writers from common pitfalls, such as reporting the chief complaint as the main diagnosis; some prompt rationale to prevent future adverse events, such as fields for medication changes and "why"; some remind providers of diagnostic tests during hospitalization, such as incidental findings or pending results; and some elicit thoughtful recommendations for postdischarge providers, such as instructions from consultants or the inpatient team.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Prior studies were limited by their use of resident educational curricula to improve discharge summaries; however, the EHR template described here uses repeated, system-level reinforcement embedded into the workflow to train residents on care transition priorities. [27][28][29] The 8-item template (Figure 2) addresses common discharge summary deficiencies reported in previous studies and confirmed in our focus groups. 6,15 Each item was created in response to PCP feedback: some items steer writers from common pitfalls, such as reporting the chief complaint as the main diagnosis; some prompt rationale to prevent future adverse events, such as fields for medication changes and "why"; some remind providers of diagnostic tests during hospitalization, such as incidental findings or pending results; and some elicit thoughtful recommendations for postdischarge providers, such as instructions from consultants or the inpatient team.…”
Section: Discussionsupporting
confidence: 76%
“…Continuously emphasizing important discharge elements and breaking down barriers in care transitions during residency training are key to this work. Prior studies were limited by their use of resident educational curricula to improve discharge summaries; however, the EHR template described here uses repeated, system-level reinforcement embedded into the workflow to train residents on care transition priorities 27-29. The 8-item template (Figure 2) addresses common discharge summary deficiencies reported in previous studies and confirmed in our focus groups 6,15.…”
Section: Discussionmentioning
confidence: 95%
“…The ACGME reinforces this idea by requiring competency in many milestones, including appropriate utilization and completion of health records (ICS3) milestone 50 . Several institutions have developed quality improvement projects to improve the standards and timeliness of discharge summaries, resulting in statistically significant improvements of multiple domains 51 53 . Academic and community medical institutions should consider adopting continuing medical education programs into their curriculum to promote more accurate and timely discharge summaries.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Additionally, scheduling follow-up appointments before discharge leads to increased primary care follow-up and potentially decreased readmission rate. 20 Previous studies have demonstrated improvement in the completion and quality of discharge summaries following educational interventions targeted toward medical trainees, 14,15,[21][22][23] and some have utilized quality improvement (QI) methodology. 6,24,25 However, few studies have demonstrated a sustainable change in pediatric settings in the era of electronic health record (EHR) use.…”
Section: Introductionmentioning
confidence: 99%